A new species of the alderfly genus Sialis Latreille, 1802 (Megaloptera: Sialidae) from southeastern China - Tu, Yuezheng; Zheng, Yuchen; Liu, Xingyue (Zootaxa, 2023)
Here we describe a new species of the alderfly genus Sialis Latreille, 1802 from southeastern China, namely S. kouwenkaii sp. nov. The new species appears to be related to a group of Sialis species once placed in Nipponosialis Kuwayama, 1962. Morphological differences between the new species and its closely related species are discussed.